Effect of various training modalities on vertical jump - Carlson, K.; Magnusen, M.; Walters, P. (Research in Sports Medicine, 2009)
The purpose of the present investigation was to compare the effects of weight training, training with weights and plyometrics, and training with weights and the VertiMax® on vertical jump. Subjects were 37 intercollegiate athletes assigned to one of four training groups: strength (S), strength-plyometric (P), strength-VertiMax® without arms (VNA), and strength-VertiMax® with arms (VA). Each group completed a 6-week training program. There were no statistical increases in pre-post vertical jump within all groups. There were no significant differences for posttest vertical jump between the four training groups. Pre- and posttest effect sizes were minimal across all groups. The findings of this study demonstrate that there is no difference in vertical jump among strength training, plyometric training, and jump training over a 6-week timeframe.